Komposisi Karawitan dalam Perspektif Estetika Posmodern - I Komang Sudirga (Journal of Music Science, Technology, and Industry, 2020)
Purpose: This article examines some works of musical composition which are dissected by the aesthetic approach of postmodernism. Research methods: The method used is a qualitative method by collecting data through observation, literature review, and document review (discography). Data analysis uses tri angulation of data from raw data collection (scripts), selection, processing, to drawing conclusions. Results and discussion: The idioms along with the aesthetic characteristics of postmodernism are applied to uncover the phenomenon of postmodernity in musical compositions with diverse ideas and perspectives. Even now, there have been a variety of new terms such as new music for new gamelan which are conceptually not familiar to the public and need to be discussed further.Implication: Various musical phenomena as well as aesthetic concepts have moved towards musical progression which not only breaks down shapes and structures but also musical understanding that has undergone a paradigm referring to the 'deconstruction' concepts of the search for identity in the era of local-global aesthetic struggles.